Sustainable nanocoatings surface. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2010)
With the growing awareness of nanobiocatalysts, a new ecofriendly process is paramount for advances in bioprocess technology. The use of biocatalysts for green organic synthesis, offering clean and mild reaction conditions, provides opportunities to increase productivity, efficiency, purity and quality innovations. Furthermore, this green route may expand and diversify markets for food to agrochemicals. Modern society has become increasingly dependent on fossil resources, especially crude oil that is used not only as fuel but also as a raw material for a variety of chemicals and other commodities. We focussed on the development and application of bio-based processes for effective transformations of non-renewable substrates into useful substances. By selectively combining their molecular constituents (fatty acids, glycerol, amino acids, saccharides etc), a wide variety of specialty and fine chemicals (amides, esters, epoxides, surface-active materials, etc.) can be prepared. Each of these ‘platform’ chemicals stands at the apex of a cascade of transformations that will produce hundreds of commercially important materials